Mengapa Profesional Muda Meninggalkan Pekerjaan: Peran Job Enjoyment, Dukungan Organisasi, dan Pengembangan Karier dalam Menjelaskan Motif Job Hopping - Jasmine Alvahreza Erika Minsa; Fetty Poerwita Sary (Universitas Muhammadiyah Pontianak, 2026)
This study aims to examine the effects of Perceived Organizational Support (POS), Job Enjoyment, and Career Development on job hopping motives among young professional workers in Indonesia. This research employs a quantitative approach with a descriptive and causal design. Data were collected through a questionnaire distributed to 230 respondents selected using purposive sampling, with criteria including young workers aged 21–35 years and having a maximum tenure of two years. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that Perceived Organizational Support (POS), Job Enjoyment, and Career Development each have a negative and significant effect on job hopping motives. The findings further reveal that Job Enjoyment is the most dominant factor in reducing job hopping motives among young professionals. Therefore, organizations are encouraged not only to provide formal support and career opportunities but also to actively foster a positive and enjoyable work environment to minimize job hopping motives among young employees.